2010
DOI: 10.1111/j.1742-1241.2010.02562.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effectiveness of aliskiren for the ‘real-world’ management of hypertension: multilevel modelling of 180-day blood pressure outcomes (the Belgian DRIVER Study)

Abstract: Aliskiren is safe and effective in reducing BP, improving BP control and reducing global CV risk in a 'real-world' setting and for patients in whom prior treatment failed or was not tolerated. Optimising treatment adherence and strategic medical education may be ways of improving BP outcomes in patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…A recent 24-week, open-label, single-arm study showed that the combination therapy of aliskiren and a RAAS blocker in CKD patients who were already being treated with ACE-is or ARBs for more than six months had a favorable effect on reducing residual proteinuria and BP reduction. 44 Another recent study 43 confirmed the efficacy and safety of aliskiren in a real-life setting. Aliskiren is approved for treatment of hypertension, but has also shown renoprotective potential in normotensive patients with T2DM and albuminuria.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent 24-week, open-label, single-arm study showed that the combination therapy of aliskiren and a RAAS blocker in CKD patients who were already being treated with ACE-is or ARBs for more than six months had a favorable effect on reducing residual proteinuria and BP reduction. 44 Another recent study 43 confirmed the efficacy and safety of aliskiren in a real-life setting. Aliskiren is approved for treatment of hypertension, but has also shown renoprotective potential in normotensive patients with T2DM and albuminuria.…”
Section: Discussionmentioning
confidence: 92%
“…However, our results are in agreement with the findings of other clinical trials. [42][43][44] An eight-week, double-blind, multicentre trial 45 assessed whether the combination of aliskiren and ramipril in patients with diabetes and hypertension was safe and effective in lowering BP when compared with the respective monotherapies. In this study aliskiren showed higher SBP reduction with ramipril.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of treatment, mean SBP/SDP reductions were 22.9 ± 16.7/10.5 ± 10.9 mm Hg ( p < 0.001). Adequate BP control based on 2009 guidelines was achieved by 56.3% of patients ( p < 0.001) and 64.2% of eligible patients had a CV risk reduction [92]. In data derived from the Italian web-based drug-monitoring system, ALI prescribed in patients with uncontrolled BP and organ damage or comorbidities produced lower SBP/DBP measurements consistently on follow-up visits, and very few reported AEs [93].…”
Section: Aliskiren and Blood Pressure Loweringmentioning
confidence: 99%
“…Furthermore, in 2007, the FDA approved Aliskiren, a first-in-class direct renin inhibitor representing the first novel therapeutic anti-hypertensive class approved by the agency in thirteen years. Although results from three clinical trials and several observational studies supported Aliskiren’s effectiveness in reducing blood pressure [7,8,9,10,11,12], evidence also suggests Aliskiren is associated with higher rates of adverse events compared with placebo in diabetic patients concomitantly treated with ARBs or ACE inhibitors [13]. …”
Section: Introductionmentioning
confidence: 99%